Peranan Kepemimpinan Kepala Sekolah dalam Peningkatan Kinerja Guru - Laeliyah, Rokhu Dlotul; Hanif, Mamun (EL-Hadhary: Jurnal Penelitian Pendidikan Multidisiplin, 2024)
Development in an educational institution is very dependent on the leadership of the school principal. An educational institution is said to be of quality if the educational institution is able to play an active role in educating the nation's life. The principal's leadership role must include the ability to guide, supervise, motivate, open two-way communication, and assign assignments. The principal must be able to carry out an educational leadership role in the school. This research aims to determine the role of school principal leadership in improving teacher performance. The method used in this research is qualitative methods, the type of research used in this research is a literature review. The leadership of the school principal greatly influences teacher performance, because with good leadership it will be easy to achieve educational goals in an educational institution. The school principal functions as an educator, manager, administrator, supervisor, leader, innovator, and also as a motivator. The role of the school principal in improving teacher performance is by increasing teacher competency through training, creating a conducive school culture, and providing rewards for teacher performance.